Source-explicit estimation of brown carbon in the polluted atmosphere over the North China Plain: implications for distribution, absorption, and the direct radiative effect - J. Zhou; J. Zhou; J. Wu; X. Su; R. Wang; I. EI Haddad; X. Li; Q. Jiang; T. Zhang; W. Dai; J. Cao; A. S. H. Prevot; et al. (Atmospheric Chemistry and Physics, 2025)
Brown carbon (BrC) plays a significant role in altering atmospheric radiation. Beyond biomass and biofuel combustion, recent studies identify fossil fuel sources – especially residential coal burning and vehicle exhaust – as major contributors to BrC. This underscores a gap in climate models, which often assume fossil fuel organic aerosols (OAs) are non-absorbing or treat all OA as light-scattering. In this study, we simulate BrC over the North China Plain (NCP) during a winter pollution event using the WRF-Chem model, incorporating explicit BrC absorption properties. The model aligns well with observed pollutant and aerosol levels, revealing an average near-surface BrC concentration of 5.2 µg m−3, contributing 16.4 % to aerosol absorption at 365 nm. Using a diagnostic adjoint approach, we estimate that BrC exerts a direct radiative effect (DRE) averaging −0.09 W m−2 at the top of the atmosphere, reducing the cooling effect of organic carbon by 28.0 % and producing a local warming effect of up to +0.40 W m−2. Coal combustion is the largest BrC source in the NCP in 2014, though secondary BrC also significantly impacts the regional radiation balance.